2009
DOI: 10.1002/glia.20846
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral myelin protein 22 is regulated post‐transcriptionally by miRNA‐29a

Abstract: Peripheral myelin protein 22 (PMP22) is a dose-sensitive, disease-associated protein primarily expressed in myelinating Schwann cells. Either reduction or overproduction of PMP22 can result in hereditary neuropathy, suggesting a requirement for correct protein expression for peripheral nerve biology. PMP22 is post-transcriptionally regulated and the 3′untranslated region (3′UTR) of the gene exerts a negative effect on translation. MicroRNAs (miRNAs) are small regulatory molecules that function at a post-transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 66 publications
3
106
2
1
Order By: Relevance
“…Earlier studies have revealed that PMP22 expression is regulated transcriptionally by cyclic AMP [25] and post-transcriptionally by microRNA-29a [27]. The relationship between these regulatory processes and the present results is currently unclear.…”
Section: Interleukin-6 Upregulates the Expression Of Pmp22 In Culturementioning
confidence: 53%
“…Earlier studies have revealed that PMP22 expression is regulated transcriptionally by cyclic AMP [25] and post-transcriptionally by microRNA-29a [27]. The relationship between these regulatory processes and the present results is currently unclear.…”
Section: Interleukin-6 Upregulates the Expression Of Pmp22 In Culturementioning
confidence: 53%
“…Apart from having roles in neuronal cell differentiation, miR-29a also is seen to be down-regulated in Schwann cells which are in proliferative and differentiating stages, in vitro in culture and in vivo during development, and after sciatic nerve injury (Verrier et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It harbors no associated mutations in its coding exons, alternative first exons 1A or 1B or adjacent sequences nor in a recently described microRNA binding site in its non-coding 3¢ tail. 28 A search for mutations in TEKT3 that is located within the duplication also did not yield any abnormalities suggesting that this 186-kb duplication is in fact responsible for the disease. TEKT3 is primarily expressed in the male germ lineage in which it is believed to be involved in spermatozoa transport 29 with a much lower expression in brain.…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded mutations in a recently described region in the PMP22 3¢UTR targeted by miR-29a that was shown to regulate expression of PMP22. 28 The TEKT3 gene that is located within the duplication was additionally examined for mutations but again, only polymorphisms were encountered (Figure 1).…”
Section: Mapping Of the Duplication And Identification Of A Junction mentioning
confidence: 99%